AN ANALYSIS OF THE DETERMINANTS OF REGIONAL ECONOMIC EFFICIENCY IN INDONESIA - Nadila Fitriansyah; Marselina Marselina (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
Lampung Province faces significant challenges in improving economic efficiency amid ongoing regional development dynamics. Despite various infrastructure development programs and economic capacity enhancement efforts implemented up to 2024, the efficient use of resources remains uneven across districts. This study aims to analyze the influence of road infrastructure, labor force, Regional Original Revenue (PAD), and General Allocation Fund (DAU) on economic efficiency in Lampung Province, while also providing a contextual comparison with other regions such as DKI Jakarta, Bali, and Kalimantan. The analysis employs a panel data multiple regression method using a sample of 15 regencies/cities in Lampung over the period 2019–2023, resulting in a total of 75 observations. The results indicate that all four independent variables have a positive and significant impact on economic efficiency. Compared to other regions, Lampung needs to strengthen infrastructure connectivity and local fiscal management to foster more equitable and sustainable efficiency gains.